2011
DOI: 10.1111/j.1346-8138.2011.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear immunoglobulin A/immunoglobulin G bullous dermatosis associated with Vogt-Koyanagi-Harada disease

Abstract: Vogt-Koyanagi-Harada disease is characterized by marked bilateral uveitis associated with symmetric vitiligo, alopecia, poliosis and dysacousia. Linear immunoglobulin (Ig)A bullous dermatosis (LABD) is characterized by small, tense, subepidermal bullae caused by IgA type autoantibody targeting the basal lamina. LABD patients sometimes show coexistence of IgG type autoantibody, termed linear IgA/IgG bullous dermatosis (LAGBD). We reported a 35-year-old Japanese male case of combined LAGBD and Vogt-Koyanagi-Hara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Recently, immunoblot studies have indicated that LAGBD sera show circulating IgA and IgG antibodies reactive with various autoantigens: BP230, BP180 NC16a domain, 97/120‐kDa LAD‐1, BP180 C‐terminal domains, laminin‐332, 290‐kDa type‐VII collagen and 200‐kDa laminin‐γ1 . Our patient showed that IgG antibodies reacted with the BP180 NC16a domain and 120‐kDa LAD‐1 in immunoblotting analyses, and IgG antibodies to BP230 in ELISA.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Recently, immunoblot studies have indicated that LAGBD sera show circulating IgA and IgG antibodies reactive with various autoantigens: BP230, BP180 NC16a domain, 97/120‐kDa LAD‐1, BP180 C‐terminal domains, laminin‐332, 290‐kDa type‐VII collagen and 200‐kDa laminin‐γ1 . Our patient showed that IgG antibodies reacted with the BP180 NC16a domain and 120‐kDa LAD‐1 in immunoblotting analyses, and IgG antibodies to BP230 in ELISA.…”
Section: Discussionmentioning
confidence: 52%
“…They stated that direct IF of a lung biopsy specimen revealed deposition of IgA, IgG and C3 along the epithelial cell membrane and basement membrane of bronchioles and alveoli. Yanagihara et al . reported a case of concurrent LAGBD and VKHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only seven patients with LAGBD with multiple autoantibodies have been reported previously (Table ) . Most of these cases showed reactivity with laminin‐332 and/or BP180.…”
Section: Linear Iga/igg Bullous Dermatosis Cases With Multiple Autoanmentioning
confidence: 99%